Translations of children’s literature into Galician (1968-1978) - Domínguez Pérez, Mónica (Madrygal. Revista de Estudios Gallegos, 2011)
Galician children’s literature was formed between 1968 and 1978, thanks to indigenous works and to the contribution of translations. An overview of the mentioned period will be presented in this article, paying special attention to translations from abroad. It will be observed thus, that translations lacked planning, but pointed to certain tendencies and contributed to the formation of the Galician children’s literature through the introduction of new literary models.